Bioarchaeology of East Asia movement, contact, health - Pechenkina, Ekaterina A. (Ekaterina Alexandrovna).; Oxenham, Marc.; Larsen, Clark Spencer (Gainesville University Press of Florida, 2013)
"Examines current understandings of human population histories, adaptations, dietary changes, and health variations within the geographical context of ancient east Asia."--Cover.
1. Research on human skeletal biology in East Asia: a historical overview Kate Pechenkina and Marc Oxenham -- 2. Human ecology in continental and insular East Asia Kate Pechenkina and Marc Oxenham -- Part 1: Biological indicators of population histories in East Asia -- 3. The population history of China and Mongolia from the Bronze Age to the Medieval period (2500 BC-AD 1500) Christine Lee -- 4. Mongolian origins and cranio-morphometric variability: Neolithic to Mongolian Period Tumen Dashtseveg -- 5. A nonmetric comparative study of past and contemporary Mongolian and Northeast Asian crania Erdene Myagmar -- 6. Tuberculosis and population movement across the Sea of Japan from the Neolithic Period to the Eneolithic Takao Suzuki -- 7. Biological connections across the Sea of Japan: a multivariate comparison of ancient and more modern crania from Japan, China, Korea, and Southeast Asia Michael Pietrusewsky -- 8. Population dispersal from East Asia into Southeast Asia: evidence from cranial and dental morphology Hirofumi Matsumura and Marc Oxenham. Part II. Community health. 9. Conflict and trauma among nomadic pastoralists on China?s northern frontier Jacqueline T. Eng and Zhang Quanchao -- 10. Stresses of life: a preliminary study of degenerative joint disease and dental health among ancient populations of Inner Asia Michelle L. Machicek and Jeremy J. Beach -- 11. Dental wear and oral health as indicators of diet among the early Qin People: a case study from the Xishan site, Gansu Province Wei Miao, Wang Tao, Zhao Congcang, Liu Wu, and Wang Changsui -- 12. Yangshao oral health from West to East: effects of increasing complexity and contacts with neighbors Kate Pechenkina, Ma Xiaolin, Fan Wenquan, Wei Dong, and Zhang Quanchao -- 13. Life on the frontier: the paleopathology of human remains from the Chinese Early Imperial Taojiazhai Mortuary site Zhang Jinglei -- 14. Bioarchaeological perspectives on systemic stress during the agricultural transition in prehistoric Japan Daniel H. Temple and Clark Spencer Larsen -- 15. Change in the linear growth of long bones with the adoption of wet-rice agriculture in Japan Kenji Okazaki -- 16. Trauma and infectious disease in Northern Japan: Okhotsk and Jomon Marc Oxenham, Hirofumi Matsumura, and Allison Drake -- 17. A paleohealth assessment of the Shih-San-Hang site from Iron Age Taiwan Liu Chin-Hsin, John Krigbaum, Tsang Cheng-Hwa, and Liu Yi-Chang -- 18. Trajectories of health in early farming communities of East Asia Kate Pechenkina, Ma Xiaolin, and Fan Wenquan -- 19. East Asian bioarchaeology: major trends in a temporally, genetically, and eco-culturally diverse region Marc Oxenham and Kate Pechenkina.
Keywords: Human remains (Archaeology) -- East Asia; Excavations (Archaeology) -- East Asia; Human skeleton -- Analysis; Paleopathology -- East Asia; Paleoanthropology -- East Asia; East Asia -- Antiquities